Structural features of the rats’ gingival mucosa lamina propria under the influence of methacrylate. - Garets, V. I.; Fedonyuk, L. Ya.; Shevchenko, K. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. At present, the need for the manufacture of removable dentures reaches 30-40% of the total number of patients seeking orthopedic care. However, one of the problems of dentistry is the adaptation to these structures, since the latter can cause various complications in patients. The study of the histofunctional features of the oral mucosa under the influence of methacrylate is of extreme urgency, both theoretical and clinical. Objective. The purpose of the paper was to determine the dynamics of changes in the structure of the attached portion of the rats’ gum under the influence of methacrylate. Methods. Twenty-five white male rats were used in the study-control (5 animals) and experimental -20 animals, treated with the oral mucosa with a 1% solution of methyl methacrylic acid for 30 days. After euthanizing animals on days 14 and 30, fragments of the attached part of the mucous membrane of the gum were emdided into epon-812. Semithing slices were stained with a polychrome dye. Morphometric studies and microphotography were carried out using a Biorex-3 BM-500T microscope. Determined the average thickness of the lamina propria, the diameters of the arterioles, capillaries and venules, the average number of migrant cells in the field of view. Statistical processing of the morphometric data was carried out according to generally accepted statistical methods using the Exel program. Results. It was found that the effect of 1% solution of methacrylic acid methyl ester for 14 days leads to structural changes in the lamina propria of the mucosa of the attached portion of the gums of the rats, which are manifested by the fullness of the blood vessels of the hemocirculatory channel and perivascular edema. From the side of the hemocirculatory circulation on the 14th day of the experiment, a narrowing of the resistive link with a dilatation of up to 30 days was determined. Exchange and capacitive links reacted by expansion on the order of observation. Up to 30 days of observation, the number of mast cells increased. Conclusion. The revealed histological and morphometric changes in the mucous membrane of the attached part of the gums of the rats are caused both by the immediate irritant effect of 1% methacrylic acid methyl ester solution and changes in the microcirculation system, which leads to disruption of the trophic components of the lamina propria of the gums mucosa.